FAKTOR YANG MENYEBABKAN NARSISME PADA REMAJA : LITELATURE REVIEW - Salsabilla, Putri; Sianturi, Renta; Fitriani, Astrida; Putri Kharisma, Cut Nophyalin; Wijaya, Darsita; Prasetiyani, Denissa Safara; Aprilia, Neta Eka (STIKES Suaka Insan, 2023)
Social media has developed into a method of social relations in cyberspace, as well as a support for narcissistic behavior. Narcissistic behavior is a personality condition in which the individual constantly fantasizes about grandeur or ego, lacks empathy, wants to be admired, and wants to be respected. The purpose of this research is to find out the causes of narcissism among adolescents on social media. This article uses the narrative literature review method. The study topic chosen was a literature review, which is a research process that involves searching for research materials and identifying, analyzing, and assessing all individual research results. The results of the ten papers included in this discussion show that adolescents use social media extensively, which influences their attitudes towards narcissism, so that many adolescents experience dependence on social media and are overconfident. This study shows that the high intensity of adolescent social media use is related to their tendency to behave narcissistically, because social media is considered to provide many facilities that allow them to express their best selves. Keywords: Social Media, Narcissistic, Adolescence